Role of Trim5α in the Suppression of Cross-Species Transmission and its Defence Against Human Immunodeficiency Virus - P. Puvvada, Madhuri; S. Patel, Snehal (Current HIV Research, 2013)
Acquired Immunodeficiency Syndrome (AIDS) was discovered 30 years ago and was followed by the identification and characterization of its causative agent, Human Immunodeficiency Virus (HIV). Increasing spread of retroviral infections has impelled science to understand the evolution of retroviruses from primates to humans. In the course of evolution, host cells have developed intracellular proteins to counteract the transforming viral defence system. Such inhibitory endogenous intracellular proteins are known as restriction factors. Tripartite motif protein isoform 5 alpha (TRIM5α), Apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC), and Tetherin proteins are few important restriction factors that have been extensively studied. Several evidences have conveyed information regarding specific adaptations occurring in HIV-1 and its relatives to inhibit these host defenses; making the study more interesting. The characteristic potential of restriction factors to restrict the replication of retroviruses was enticing when studies were found that HIV-1 virus cannot infect nonhuman primate species. This review emphasizes on TRIM5α as a restriction factor and its significance in the evolution of retroviruses. It also accentuates the role of polymorphism within the regions of TRIM5α in both human and primate species that eventually affect the cross-species transmission of immunodeficiency viruses.
Keywords: Acquired immunodeficiency syndrome